PENGARUH PERENCANAAN PAJAK, MANAJEMEN LABA, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN: Studi Empiris Pada Perusahaan Subsektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia - Muhammad Maryadi; Chaidir Djohar (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine and obtain empirical evidence regarding the effect of tax planning, earnings management, and sales growth on firm value. This study uses a sample of primary consumer goods sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling method used in this study is the purposive sampling method using Eviews 9 for data analysis. The source of data in this study is quantitative data originating from the annual financial statements of 22 companies as research samples with observations for 5 years, so that the total research sample is 110 samples. The analysis technique used is panel data regression. The results of this study indicate that significantly, Tax Planning and Earnings Management have no significant effect on firm value, while significantly, sales growth has an effect on firm value. and Simultaneously, Tax Planning, Earnings Management, and Sales Growth together have an effect on Company Value